The Interaction of NDF Level and Fiber Particle Size on Productivity and Fiber Digestion in Rabbit during the Fattening Period - M. Sobri; K. G. Wiryawan; P. D. M. H. Karti; I. W. T. Wibawan (Tropical Animal Science Journal, 2019)
This research was conducted to determine the interaction of NDF level and fiber particle size on the performance of production, digestibility of dry matter, crude fiber and fiber fraction, digestive tract, microbial profiles, volatile fatty acids (VFA), and total organic acid of rabbits during the fattening period. The experiment utilized 144 New Zealand white (NZW) crossbred rabbits aged 28 days. The experimental design was a completely randomized 3 x 3 factorial pattern, with 3 levels of neutral detergent fiber (NDF) (F1= 33.60%, F2= 36.10%, and F3= 41.43%) and 3 sizes of fiber particles (P1= 1 mm, P2= 2 mm, and P3= 3 mm). Each treatment had 4 replications, and each replication had 4 animals. The combination treatment showed changes in feed intake with an average of 5.25 kg/head. The F2 treatment showed the best results in body weight gain (BWG) and feed conversion ratio (FCR) with an average of 1.80 kg/head and 3.09, respectively. The F1 level showed the highest average of pathogenic bacteria (E. coli) population at 3.37 x 109 cfu/mL which inversely proportional to the average level of butyric acid percentage and total organic acids which were 12.92% and 386.23 mmol/L in rabbits during the post-weaning period. The conclusion of this study was that the inclusion of NDF and a balanced size of fiber feed in feed could lead to optimization of the fiber digestibility, digestive tract, total organic acid production, and butyric acid concentration which could suppress the growth of E. coli and improve the performance of rabbits during the fattening period.